2017
DOI: 10.1007/978-981-10-6620-7_57
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based Big Data Analytics—A Survey of Current Research and Future Directions

Abstract: The advent of the digital age has led to a rise in different types of data with every passing day.In fact, it is expected that half of the total data will be on the cloud by 2016. This data is complex and needs to be stored, processed and analyzed for information that can be used by organizations. Cloud computing provides an apt platform for big data analytics in view of the storage and computing requirements of the latter. This makes cloud-based analytics a viable research field. However, several issues need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 20 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Data Analytics is the heart of application development in IoT Cloud environment. Number of applications can be developed using big data analytics in cloud environment [21]. Task scheduling and load balancing is required to improve efficiency of platforms [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data Analytics is the heart of application development in IoT Cloud environment. Number of applications can be developed using big data analytics in cloud environment [21]. Task scheduling and load balancing is required to improve efficiency of platforms [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the research trends identified among the recent applications is cloud computing, which provides a better solution for big data storage, transmitting and computational requirements [125]. It is also worth noting the popularity of integrating the Internet of Things [126], the architecture of a platform that enables efficient, real-time, in memory cloud computing and storage of complex big data with the most advanced analytics or data mining techniques, as well as integrating the Internet of Things is the key to future research.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…The applicability of big data technologies [6], implemented using cloud-based infrastructures, to real-world, data-intensive scenarios has given rise to many sub-research areas. Big data has particularly found applications in healthcare [7], geospatial analytics [8] and business intelligence [9], in addition to many others. Education data is a form of big data and can make use of big data technologies for generating valuable analytics for an educational organization [10].…”
Section: Related Workmentioning
confidence: 99%